Fabrication and characterization of biodegradable poly(3-hydroxybutyrate) composite containing bioglass - Boccaccini, Aldo R.; et al. (Biomacromolecules, 2007)
Bacterially derived poly(3-hydroxybutyrate) (P(3HB)) has been used to produce composite films by incorporating Bioglass particles (<5 μm) in 5 and 20 wt % concentrations. P(3HB) was produced using a large scale fermentation technique. The polymer was extracted using the Soxhlet technique and was found to have similar thermal and structural properties to the commercially available P(3HB). The effects of adding Bioglass on the microstructure surface and thermal and mechanical properties were examined using differential scanning calorimetry, dynamic mechanical analysis (DMA), X-ray diffraction, surface interferometry, electron microscopy, and nanoindentation. The addition of increasing concentrations of Bioglass in the polymer matrix reduced the degree of crystallinity of the polymer as well as caused an increase in the glass transition temperature as determined by DMA. The presence of Bioglass particulates reduced the Young's modulus of the composite. The storage modulus and the loss modulus, however, increased with the addition of 20 wt % Bioglass. A short period (28 days) in vitro bioactivity study in simulated body fluid confirmed the bioactivity of the composites, demonstrated by the formation of hydroxyapatite crystals on the composites surface. © 2007 American Chemical Society.
UnivIS-Import:2015-03-09:Pub.2007.tech.IW.LM.fabric